Responsibilities of women in promoting social values: An analytical contemporary Study in the light of Sīrahazwāj e Muṯaharāt - Dr. Fariha Anjum (jihat-ul-islam, 2026)
In Islam, where worship and affairs have primary status, religious morals and social values are of key importance. Respect for social values is the basis of the rights that Allah has enjoined on the Muslims. Prophet Muhammad (saw) serve as a teacher of ethics and a bearer of good high moralities. A society is made up of both men and women. Allah has made some difference in physical structure and their psychology, likewise Allah has divided the responsibilities and duties. A woman is responsible for family and social upbringing. According to Prophet Muhammad (saw) every child is born with pure nature, then the training affects him. This training starts from a woman as mother and then the same woman continues to fulfil her responsibilities as wife, sister and a member of society. In this regard, the life of Azwājmuṯahrāt is a practical example because they were trained by the Prophet Muhammad (saw). In this article, the responsibilities of women in promotion of social values such as good behaviour, justice, truthfulness and charity will be discussed and social and moral aspect of the lives of Azwājmuṯaharāt will be highlighted.so that the today’s woman can fulfil her responsibilities in best possible way and establish a better Islamic society.